Results of using the neuroprotective drug Cellex in non-traumatic intracranial hemorrhage - Kh. D. Mongush; A. V. Kyrgys; A. A. Sedip; A. E. Shyyrap; A. B. Ondar; M. G. Zhestikova (Медицинский совет, 2022)
Introduction. In the Russian Federation, neuroprotective agents are widely used in the treatment of patients with ischemic stroke. There are accumulated data on the efficacy and safety of the neuroprotective agent Cellex® in ischemic stroke. The use of this drug in hemorrhagic stroke has been studied to a lesser extent.Aim. To study the efficacy and safety of Cellex® in non-traumatic intracerebral hemorrhage.Materials and methods. The study included 60 patients with hypertensive intracerebral hemorrhage aged 30 to 80 years. Thirty patients (the main group) received Cellex 0.1 mg (1 ml) once a day for 10 days in addition to basic therapy; the remaining 30 patients (control group) received only basic therapy. Over the course of 30 days, the patients were evaluated for various parameters on the Glasgow Coma Scale, stroke severity on the NIHSS scale, patient disability on the Modified Rankin Scale, Barthel Index and Rivermead Mobility Index, speech disorders on the Speech Questionnaire, cognitive function on the Montreal Cognitive Scale (MoCA), and other parameters.Results and discussion. The survival rate was higher in the treatment group than in the control group (p = 0.0237). Speech function improved from 17.0 (14.0–22.0) to 25.0 (21.0–27.0) scores (p = 0.0073) in the Cellex group, no significant improvement in speech function was noted in the control group. There was a trend toward a more significant reduction in stroke severity according to the NIHSS scale and inpatient disability according to the Rankin, Barthel, and Rivermead scales in the Cellex group compared with the control group. Cognitive function on MoCA score improved in Cellex® group from 14.0 (12.0; 22.5) to 20.0 (14.5; 25.0). No adverse events were observed in the group of patients taking Cellex.Conclusion. The efficacy and safety of Cellex® in patients with hypertensive intracerebral hemorrhage has been proven.